2005
DOI: 10.1007/s00534-004-0964-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted laparoscopic Roux-en-Y choledochojejunostomy in pigs

Abstract: Robotic-assisted Roux-en-Y choledocho-jejunostomy is an easy procedure and accomplishes biliary drainage and intact intestinal flow. Decreasing operating times were experienced, approximating those of a skilled operator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Since the advent of robotic surgery, animal models using the robot have been developed [ 13 , 14 ]. Both papers described end to side CJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the advent of robotic surgery, animal models using the robot have been developed [ 13 , 14 ]. Both papers described end to side CJ.…”
Section: Discussionmentioning
confidence: 99%
“…Both papers described end to side CJ. One article described CJ using running sutures for both the posterior layer and the anterior layer [ 14 ], and the other described CJ using interrupted sutures for both layers [ 13 ]. The obvious distinction between these training models and the model introduced here is that robotic surgery was used.…”
Section: Discussionmentioning
confidence: 99%
“…smaller incisions, decreased pain and earlier return to normal functioning. Robotic biliary surgery has proved feasible in an animal model (6)(7)(8) and major biliary surgery has been conducted safely in a paediatric population (9,10), although the enteroenteric anastomoses were performed extra-corporeally. Intracorporeal enteroenteric anastomosis is routinely performed in other fields of surgery (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…In three earlier studies, we suggested alternative methods for reconstruction: using the gallbladder for a fl ap(4), utilizing a vascular prosthetic graft (5), or doing the operation as robotic-assisted by the da Vinci laparoscopic system (6). However, sometimes -maybe more often than is utilized at present -reconstruction can be done by duct-to-duct repair, which prompted us to do the present study, evaluating the natural healing of choledocho-choledochostomies.…”
Section: Discussionmentioning
confidence: 99%